Scratching the Surface—An Overview of the Roles of Cell Surface GRP78 in Cancer - Jack Chen; Edward G. Lynn; Tamana R. Yousof; Hitesh Sharma; Melissa E. MacDonald; Jae Hyun Byun; Bobby Shayegan; Richard C. Austin (Biomedicines, 2022)
The 78 kDa glucose-regulated protein (GRP78) is considered an endoplasmic reticulum (ER)-resident molecular chaperone that plays a crucial role in protein folding homeostasis by regulating the unfolded protein response (UPR) and inducing numerous proapoptotic and autophagic pathways within the eukaryotic cell. However, in cancer cells, GRP78 has also been shown to migrate from the ER lumen to the cell surface, playing a role in several cellular pathways that promote tumor growth and cancer cell progression. There is another insidious consequence elicited by cell surface GRP78 (csGRP78) on cancer cells: the accumulation of csGRP78 represents a novel neoantigen leading to the production of anti-GRP78 autoantibodies that can bind csGRP78 and further amplify these cellular pathways to enhance cell growth and mitigate apoptotic cell death. This review examines the current body of literature that delineates the mechanisms by which ER-resident GRP78 localizes to the cell surface and its consequences, as well as potential therapeutics that target csGRP78 and block its interaction with anti-GRP78 autoantibodies, thereby inhibiting further amplification of cancer cell progression.